The association between cognitive impairment and oral health or oral hygiene behaviors among multiethnic older adults in Western China: a cross-sectional multicenter study - Yuqing Xie; Xin Xia; Xin Tian; Yuexia Hu; Yun Li; Xiao Tan; Wenwen Wu; Birong Dong; Yanyan Wang (BMC Public Health)
Abstract Background Older adults with cognitive impairment tend to experience deteriorating oral health and inadequate oral hygiene behaviors, but few studies have addressed interethnic variability. This study aimed to explore the associations between cognitive impairment and oral health or oral hygiene behaviors in multiethnic older adults in Western China. Methods We conducted a cross-sectional multicenter study from four provinces of Western China, recruiting multiethnic older adults aged 50 years and older between July and December 2018. Oral health and oral hygiene behaviors were evaluated through an oral examination and a self-made questionnaire, whereas cognitive condition was assessed via the Chinese version of the Short Portable Mental Status Questionnaire (SPMSQ). Three multiple regression models were used to examine the associations between cognitive impairment and oral health or oral hygiene behaviors, with adjustments for relevant variables. Results A total of 6529 participants with a median age (interquartile range) of 62.4 (55, 68) years were included. The prevalence of cognitive impairment was 15.4%, with the Yi group having the highest prevalence (28.9%), followed by the Tibetan (19.1%) and Qiang (15.4%) groups. Poorer self-rated oral health, fewer residual teeth, less frequent use of toothbrushes and toothpaste, and irregular dental care were associated with a risk of cognitive impairment (p < 0.05). The SPMSQ scores and correlations between cognitive impairment and oral health or oral hygiene behaviors were heterogeneous among the multiethnic groups. Conclusion Inadequate oral hygiene behaviors and deteriorating oral health may be associated with a higher risk of cognitive impairment. Advancing oral health and oral hygiene behaviors is essential for preventing cognitive impairment among multiethnic older adults.